Evaluation of composite fiber-plastics biomass clinkering under the gasification conditions. (15th October 2017) - Madadian, Edris; Crowe, Christine; Lefsrud, Mark
Abstract: Cross contamination and non-recyclables remain after the separation of valuables in the recycling process, especially with commingled or single stream recycling systems. Therefore, some carbonaceous fractions of recyclables, such as plastics and fibers, are left as a potential biomass feedstock for the thermochemical or thermal conversion processes. However, this fraction of waste is more likely to be highly contaminated and challenging, or may become unpredictable during its reuse in the thermal conversion process for heat and power applications. The current study aims to find how the increase in plastic specifically in the recycled fiber stream may affect the performance of a downdraft gasifier. Therefore, the effect of plastic combined with fiber feedstock during gasification has been investigated. For this purpose, three different plastic percentages of 2%, 5%, and 10% mixed with fiber were studied. The results showed that higher plastic-containing feedstock has higher energy content; however, the higher plastic content causes mechanical performance issues inside the reactor and does not necessarily guarantee greater biomass heating value. Furthermore, gasifying the higher plastic percentage results in a temperature drop across the reactor. This change in temperature is the result of thermal reactions of fiber material mixed with plastic that generates firm clinkers and interrupts the normal conditions in the reactor. The clinker predominantly contains aluminum, silicon, calcium and sodium that originate from the source of fiber and plastic. This research has shown that a mixture of silicon with aluminum, calcium and sodium under high temperatures result in the generation of a solid clinker that ultimately moves through the reactor and deposits at the bottom of the reactor. Highlights: Biomass ash sinters and transforms to clinker within high temperature gasification. Clinker resembles to Al-Si alloys which are widely used in automotive industry. Composition and history of composite constituents affect the thermal properties. TPS technique used to measure thermal conductivity of unknown plastic wastes. The higher volume fraction of plastic led to higher amount of clinker.